Análise das características estruturais do FAD em oxidorredutases - Silva, Rui Filipe Nogueira da (Universidade Federal de São Carlos, 2015)
In this work, oxidoreductases of the glutathione reductase (GR), trypanothione reductase (TR) and sulfhydryl oxidase (SOX) sub-subclasses that are FAD (flavin adenine dinucleotide) dependent enzymes and contain a group with sulfur as a charge acceptor/donor near the FAD isoalloxazine region were studied. Oxidoreductases are enzymes capable of catalyzing redox reactions, thus requiring donor groups and acceptor groups of charges. FAD is a cofactor of the oxidoreductases and participates in the enzymatic catalysis, brokering the transfer of charges between ligands and the polypeptide chain of the proteins. The thiol groups and disulfide bonds existing in the enzymes are, in many instances, involved in these transfer of protons and electrons together with the FAD. The conformation of the isoalloxazine region of the FAD and the π interactions between the sulfur atoms and the flavin region were studied. The crystal structures of 180 oxidoreductases with FAD and disulfide bonds retrieved from the Protein Data Bank (PDB) were analyzed, which allowed to set up some relationships between the bond lengths of the disulfide bridge in proteins and in small molecules, to determine the existence of deformations of the isoalloxazine moiety of the FAD, to measure the SG-π interaction distances and realize some FAD features that help differentiate the GR, TR and SOX sub-subclasses.
Keywords: Biotecnologia; Glutationa redutase; Oxidorredutases; Tripanotiona redutase; FAD; π interactions; Dissulfide; S-π; Oxidorreductases; Glutathione reductase; Trypanothione reductase; Sulfhydryl oxidase; CIENCIAS EXATAS E DA TERRA::FISICA; CIENCIAS EXATAS E DA TERRA::QUIMICA